A descriptive-contrastive analysis of Chabacano and Tagalog noun reduplication patterns - Batausa, Corazon (De Castro) 1933- (s.n.], 1969)
This is a descriptive-contrastive analysis of Chabacano and Tagalog noun reduplication patterns in the objective of discovering the basic similarities and differences between reduplication patterns of the two languages in terms of form, meaning, and distribution.